Medial and Lateral Discoid Menisci of Both Knees - Kan, Hiroyuki (Knee Surg Relat Res, 2016)
Discoid menisci on both the medial and lateral sides are rare, and there are very few reports on cases involving both sides. We report a case of a 52-year-old female with medial and lateral discoid menisci in both knees. Arthroscopy revealed the lateral menisci of both knees were complete discoid menisci, and partial meniscectomy was performed. The medial menisci were incomplete discoid menisci, but there were no findings of abnormal mobility or injury; therefore, the medial menisci were observed without treatment. At six months postoperatively, her pain and range of motion restrictions disappeared.